Case Study: Deep Breath Intervention to Reduce Pain in Mild-head Injury Patients - Ade Fitriani; Riska Fadilah; Dea Sri Suhartini; Aap Apipudin; Yanti Srinayanti (Inspirasi Foundation, 2023)
Objective: To present upbringing with deep breath intervention to reduce pain in patients with mild head injuries. Methods: The method used is descriptive with a case study approach using nursing care that refers to the SDKI and SIKI books. The subjects in this study were 1 patient with a nursing diagnosis of acute pain in a patient with a minor head injury at the orchid room of the Banjar City Hospital. With data collection techniques include interviews, observations, physical examinations and documentation studies. Results: From nursing care in patients with chronic renal failure, the symptom that appears at the time of the assessment is pain. The nursing problem that arises is that acute pain is related to physical injury agents referring to the SDKI book. The intervention carried out to reduce pain is by deep breath relaxation techniques. During the intervention process, the action went smoothly until the evaluation. There are changes in pain. Conclusion: After deep breath intervention there was a change in pain from a scale of 5 to 2 (0-10), while the results of anamnesis obtained subjective data, the client said the pain was reduced.